Probing the Viability of Scopus-Indexed Journal Quantity as Alternative Metric for Knowledge Capital: Evidence From Selected ASEAN+3 Economies - Rivera, John Paolo R. (Animo Repository, 2021)
With Industry 4.0, the role of research cannot be undermined. As innovations drive the economy, we explicated the contribution of knowledge capital to the macroeconomy. Following the endogenous growth theory, we estimated a three-factor Cobb-Douglas aggregate production function for selected ASEAN+3 economies. Using the total number of Scopus-indexed journals as our proposed alternative metric for knowledge capital, we found that investing in the creation of more scientific researches and using it as productive inputs allow an economy to experience growth in the long run. Results showed that increasing knowledge capital, constituting higher levels of research, creates new technologies and innovations that stimulate economic growth.